2014
DOI: 10.1007/s12010-014-1120-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Particle Size and Densification on AFEX-Pretreated Biomass for Ethanol Production

Abstract: Switchgrass (SG), corn stover (CS), and prairie cordgrass (PCG) pretreated with ammonia fiber expansion (AFEX) were densified using a novel low-temperature, low-pressure densification method. Simultaneous saccharification and fermentation (SSF) and separate hydrolysis and fermentation (SHF) were performed with loose and densified AFEX-treated biomass to determine the effect of post-AFEX densification. Biomass particle size reduction before pretreatment increased 144-h SSF ethanol yields from densified material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Additional studies have been performed quantifying ethanol yields from densified AFEXpretreated corn stover, switchgrass, and prairie cordgrass. Rijal et al [69] studied the effect of initial particle size (2, 4, 8 mm) and densification on ethanol production. They employed a novel densification method, ComPAKo that uses a gear, mesh system to produce compacted biomass briquettes (1 inch × 0.5 inch × 4 inch).…”
Section: Compako Briquettesmentioning
confidence: 99%
“…Additional studies have been performed quantifying ethanol yields from densified AFEXpretreated corn stover, switchgrass, and prairie cordgrass. Rijal et al [69] studied the effect of initial particle size (2, 4, 8 mm) and densification on ethanol production. They employed a novel densification method, ComPAKo that uses a gear, mesh system to produce compacted biomass briquettes (1 inch × 0.5 inch × 4 inch).…”
Section: Compako Briquettesmentioning
confidence: 99%
“…Comparative studies between wet and dry milling showed that ~5% more ethanol yields with wet milling process, dry milling process and the average oil content of germ was 10% more 17,18,42 . Pretreatment cost of directly fermentable sugar containing materials is less, whereas indirectly fermentable starchy materials need costly pretreatment to convert them into fermentable substrates 52 .…”
Section: Ethanol From Gasification Of Lignocellulosic Biomassmentioning
confidence: 99%
“…Introduction Lignocellulosic biomass, for example corn stover, switchgrass, and prairie cord grass are widely available and can be converted through wide range of technologies to different forms of energy, chemicals, and materials [1,2]. Efficient conversion of biomass into bioenergy relies heavily on the effective, consistent, and economical transport of biomass from field to the biorefinery.…”
mentioning
confidence: 99%
“…ND) was used to compact the AFEXpretreated switchgrass, corn stover, and prairie cord grass of different grind sizes (2 mm, 4 mm, and 8 mm). Unlike the commercial ring die pelleting units, this system uses a gear and mesh system to compress the biomass [1]. The system operates at relatively low temperatures (ambient to 60 C) and pressures with low energy input (180 HP motor to produce 7e8 tons/h).…”
mentioning
confidence: 99%
See 1 more Smart Citation